2013
DOI: 10.1210/en.2013-1142
|View full text |Cite
|
Sign up to set email alerts
|

GPR41/FFAR3 and GPR43/FFAR2 as Cosensors for Short-Chain Fatty Acids in Enteroendocrine Cells vs FFAR3 in Enteric Neurons and FFAR2 in Enteric Leukocytes

Abstract: The expression of short-chain fatty acid receptors GPR41/FFAR3 and GPR43/ free fatty acid receptor 2 (FFAR2) was studied in the gastrointestinal tract of transgenic monomeric red fluorescent protein (mRFP) reporter mice. In the stomach free fatty acid receptor 3 (FFAR3)-mRFP was expressed in a subpopulation of ghrelin and gastrin cells. In contrast, strong expression of FFAR3-mRFP was observed in all cholecystokinin, glucose-dependent insulinotropic peptide (GIP), and secretin cells of the proximal small intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
432
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 471 publications
(447 citation statements)
references
References 46 publications
13
432
1
1
Order By: Relevance
“…Similar to K þ efflux, we found that acetate mediated hyperpolarization through GPR43 and activated the inflammasome in colonic epithelial cells. As described for neutrophils 12,33 , acetate induced an increase in intracellular Ca 2 þ in colonic epithelial cells, which is in accordance with other reports showing enteroendocrine cells expressing GPR43 mobilize Ca 2 þ when stimulated with agonist 34 . An increase of intracellular Ca 2 þ has been shown to promote K þ efflux in HT29 cells, suggesting that the hyperpolarizing effects of acetate might be due indirectly to a rise in intracellular Ca 2 þ (ref.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to K þ efflux, we found that acetate mediated hyperpolarization through GPR43 and activated the inflammasome in colonic epithelial cells. As described for neutrophils 12,33 , acetate induced an increase in intracellular Ca 2 þ in colonic epithelial cells, which is in accordance with other reports showing enteroendocrine cells expressing GPR43 mobilize Ca 2 þ when stimulated with agonist 34 . An increase of intracellular Ca 2 þ has been shown to promote K þ efflux in HT29 cells, suggesting that the hyperpolarizing effects of acetate might be due indirectly to a rise in intracellular Ca 2 þ (ref.…”
Section: Discussionsupporting
confidence: 92%
“…Signaling through GPCRs, as well as transport of SCFAs by SLC5A8 and the resultant physiological effects, are affected by dietary intake of fermentable fiber (128). Different types of SCFA receptors have been identified on enteroendocrine cells and on neurons of the submucosal and myenteric ganglia (129). A diet supplemented with Bifidobacterium breve was associated with increased fatty acid concentrations in the brain; however, the mechanisms underlying these effects are not known (75).…”
Section: Effect Of Interventions Targeting the Gut Microbiotamentioning
confidence: 99%
“…They have been identified as ligands for two GPCRs, free fatty acid receptor 2 (FFAR2, previously known as GPR43) and FFAR3 (previously known as GPR41) (102,103), both of which are detectable in rat and human colonic mucosa (104)(105)(106) and in murine L cells (106)(107)(108). FFAR2 couples to G q and G i pathways, whereas FFAR3 is presumed to couple exclusively to the pertussis toxin-sensitive G i pathway (102,103).…”
Section: Gut Microbiota Host Defense and Eec Signalingmentioning
confidence: 99%